Intimacy negotiated: the management of relationships and the construction of personal communities in the lives of bisexual women and men - Toft, Alex; Yip, Andrew Kam-Tuck (Sage, 2018)
Bringing into dialogue conceptual literature on bisexuality, intimacy, and personal community, this article illuminates the lived experiences of 80 bisexual women and men in the UK. The data were collected through questionnaire and individual interview. The article discusses two empirical themes, beginning with the participants’ narratives on their engagement with the dominant sexual and gender order – which hegemonizes ‘monosexuality’ and ‘compulsory monogamy’ – in their negotiation of relational intimacy. This is followed by an exploration of the features and functions of their personal communities, especially the significance of friendships. The article argues that, despite the ambivalence and misperception surrounding bisexuality, the participants enacted creative agency in negotiating intimacy and social support in their everyday lives.